Graphene-based porous nanohybrid architectures for adsorptive and photocatalytic abatement of volatile organic compounds. (15th September 2022) - Bilal, Muhammad; Rizwan, Komal; Rahdar, Abbas; Badran, Mohamed Fathy; Iqbal, Hafiz M.N.
Abstract: Volatile organic compounds (VOCs) represent a considerable threat to humans and ecosystems. Strategic remediation techniques for the abatement of VOCs are immensely important and immediately needed. Given a unique set of optical, mechanical, electrical, and thermal characteristics, inimitable surface functionalities, porous structure, and substantial specific surface area, graphene and derived nanohybrid composites have emerged as exciting candidates for abating environmental pollutants through photocatalytic degradation and adsorptive removal. Graphene oxide (GO) and reduced graphene oxide (rGO) containing oxygenated function entities, i.e., carbonyl, hydroxyl, and carboxylic groups, provide anchor and dispersibility of their surface photocatalytic nanoscale particles and adsorptive sites for VOCs. Therefore, it is meaningful to recapitulate current state-of-the-art research advancements in graphene-derived nanostructures as prospective platforms for VOCs degradation. Considering this necessity, this work provides a comprehensive and valuable insight into research progress on applying graphene-based nanohybrid composites for adsorptive and photocatalytic abatement of VOCs in the aqueous media. First, we present a portrayal of graphene-based nanohybrid based on their structural attributes (i.e., pore size, specific surface area, and other surface features to adsorb VOCs) and structure-assisted performance for VOCs abatement by graphene-based nanocomposites. The adsorptive and photocatalytic potentialities of graphene-based nanohybrids for VOCs are discussed with suitable examples. In addition to regeneration, reusability, and environmental toxicity aspects, the challenges and possible future directions of graphene-based nanostructures are also outlined towards the end of the review to promote large-scale applications of this fascinating technology. Graphical abstract: Image 1 Highlights: Volatile organic compounds (VOCs) signify threat to human's health and ecosystem. Graphene-derived nanostructures as prospective platforms for VOCs degradation. Adsorption and photocatalytic performance of graphene nanohybrids for VOC removal. Regeneration, reusability, environmental toxicity, and stability aspects are outlined.